(untitled) (Zia e Tahqeeq, 2021)
The article studies the role of letters in deducing the rulings from the Noble Quran. The Holy Quran lies in its worth as the Words of Allah who says in the Holy Quran, "Verily this Quran guides towards the straight path"; and it is not possible to get the guidance without understanding its commandments. The Holy Quran was revealed in the Arabic language as the Arabs who were its first audience. Therefore, to understand its commandments and to attain its guidance, it is indispensable to learn the Arabic language with its rhetoric. The Islamic jurists differed from one another in the interpretation and exegesis of the Quran due to the rich rhetoric and the wide linguistic diversity of the Arabic language and not due to their inclinations or mindsets, developed within the circles of particular schools of thought. The differences in the interpretations of the Quranic commandments are found frequently in the Islamic jurists and the scholars of the exegesis due to the rich linguistic rhetoric of the Arabic language. Hence, it proves that in the derivation of the Quranic laws, the role of the Arabic language can not be ignored.